An observability form for linear systems with unknown inputs - Floquet, T.; Barbot, J. P. (International journal of control, 2006)
In this paper is given a constructive algorithm that transforms a linear system with unknown inputs into a novel observability form. This form is useful to derive finite time observers even if the system does not satisfy some matching conditions usually required for the design of unknown input observers. The practical example of an aircraft subject to actuator faults is provided to show the efficiency of the approach.